PROPERTIES OF DIFFERENT GENOTYPES OF SILAGE MAIZE HYBRIDS - Nikolić, Valentina (Food and Feed Research, 2020)
The aim of this study was to observe the properties of ten maize hybrids from Serbia including agronomic traits, lignocellulosic fibre composition and in vitro dry matter digestibility. Five yellow kernel dent hybrids and five analogue red kernel hybrids were used in this study to evaluate the agronomic traits, dry matter content of the whole plant, lignocellulosic fibre composition, ratios between different fibres, in vitro dry matter and NDF digestibility. Correlation coefficients between the investigated traits of the maize hybrids were assessed. Even though the results of our study showed variations regarding nutritional composition of the whole maize plant between the investigated maize hybrids, the hybrid and the differences in kernel colour (yellow or red) did not considerably affect the properties that influence quality of the maize hybrids for silage production. The highest IVDMD was determined in yellow kernel hybrid ZP 388, while the maximum NDFD was detected in the red kernel hybrid ZP 606red which also showed the lowest ADL/NDF and ADF/NDF ratios. The results indicate that all of the hybrids used in this study are good candidates for the production of high-quality silage for ruminant nutrition.